Congenital Anomalies and Termination of Pregnancy in Iran. (24th April 2012) - Samadirad, Bahram; Khamnian, Zhila; Hosseini, Mohammad Bager; Dastgiri, Saeed
Abstract : The aim of this study was to document some epidemiological features of termination of pregnancy for birth defects in Iran. We studied 603 pregnant women who were diagnosed/recommended for the termination of pregnancy as having a fetus with some types of birth defect(s). Most women (87.2 percent) had at least one ultrasound examination. The proportion of other screening tests including amniocentesis and genetic tests were 2.8 and 4.6 percent, respectively. Of 603 women, 201 terminated the pregnancy giving a prevalence rate of 33.3 percent (CI 95%: 29.6–37.6). The remaining 402 subjects were unable to get the permission for abortion because of untimely diagnosis/application for termination (20th week of pregnancy and/or later). Forty-eight percent of termination of pregnancies was performed before the 18th week of pregnancy. Neural tube defects, limb deformation, hydrops fetalis, hydrocephaly, and chromosomal anomalies including Down syndrome accounted proportionally for about 65 percent of defects eligible for abortion in the region. Although the rate of termination of pregnancy for birth defects is acceptable at the current situation in the country, more efforts should still be made to convince the community authorities to give more possibility and ease for the termination of pregnancy for congenital anomalies.